A simple relativistic model of p(p)over-bar-]K+K- - Frederico, T.; Dey, Jishnu; Tomio, Lauro [UNESP] (Elsevier, 1995)
We compare a model calculation with some available experimental data (LEAP 92) on KK̄ production. We believe the simplicity of the model makes it a useful tool for studying charm and beauty baryon production, for which also experimental data will soon be profuse.